The impact of epigenetics on tumor metabolism: Friend or foe in drug response? - Castelli, Serena; Franchini, Melania; Ferraro, Luigi; Mangraviti, Nicolò (Frontiers in Epigenetics and Epigenomics, 2026)
Cancer cells exhibit remarkable plasticity, enabling them to survive therapeutic pressure by dynamically rewiring both their epigenetic landscape and metabolic circuitry. Emerging evidence reveals that epigenetic mechanisms, including DNA methylation, histone modifications, chromatin remodeling, and non-coding RNAs, are tightly coupled to metabolic pathways through key metabolites that function as cofactors or regulators of chromatin-modifying enzymes. This reciprocal interplay establishes self-reinforcing loops that sustain tumor growth, promote heterogeneity, and drive the emergence of drug-tolerant states. In this review, we summarize current knowledge on how epigenetic remodeling shapes metabolic reprogramming and, in turn, how altered metabolite pools influence chromatin states in cancer. We highlight the central role of long non-coding RNAs and other ncRNA species in coordinating epigenetic and metabolic adaptations that underpin therapy resistance. We further examine the contribution of metabolite-dependent post-translational modifications, such as acetylation, methylation, lactylation, and succinylation, to the regulation of tumor aggressiveness and treatment response. Finally, we discuss how multi-omics integration, computational network approaches, and AI-enabled modeling are accelerating the discovery of epigenetic–metabolic vulnerabilities and informing the development of precision therapeutic strategies. Understanding and targeting this epigenetic–metabolic axis holds substantial promise for overcoming drug resistance and improving the durability of cancer therapies.